Analysis of the electrodynamic model of a biologically active point of animal skin - Гузенко, В.В.; Семенець, В.В.; Носова, Т.В.; Лисиченко, М.Л.; Косуліна, Н.Г. (Radiotekhnika, 2020)
Flat-layered dielectric structure was considered as an electrodynamic model of bioactive point (BAP). This structure is formed by three flat dielectric layers and eventual cylinder filled by a dielectric (by the albumen of collagen). The upper layer designs burly cages, middle layer is blood and lymphatic vessels and an understratum is formed by nervous fibres that conduct and pass management signals from BAP to the central nervous system. Such electrodynamic structure is the dielectric resonator (eventual cylinder) located in a dielectric environment. We will examine affecting of informative electromagnetic radiation on bioactive point, the wave-length of which considerably excels geometrical sizes bioactive point. This fact allows averaging of material parameters on a coordinate . Therefore, it was assumed further, that material parameters (dielectric constant) of flat layered structure (model of bioactive point) does not depend on a coordinate , i.e. the electromagnetic field is axisymmetric. Such electromagnetic field can be excited by the circular electric current located at some distance from the external surface of bioactive point. It was supposed that this current excited harmonic oscillation with circular frequency and modulated on amplitude with frequency of modulation . The problem of the interaction of radio-pulse waves with a biologically active point is an unsteady diffraction problem. Using the complex amplitude method, this problem was reduced to the diffraction problem for electromagnetic fields that depend exponentially on time. By virtue of the principle of superposition, the solution to the original problem can be obtained as a superposition of the solutions of three problems using the complex amplitude method. Such electrodynamic structure allows defining the necessary parameters of the informative electromagnetic field for treatment of dyspepsia of newborn calves.